MOLECULAR MARKERS FOR VEGETABLE PEA SAMPLES - V. S. Anokhina; I. B. Sauk; Y. I. Romanchuk; S. S. Zhardetskiy; S. M. Dronov; A. I. Chaikovskiy (Овощи России, 2015)
The paper presents the results of research on the presence in genomes of pea hybrid materials of the DNA regions complementary to the primers that are associated with the biochemical characteristics and resistance to powdery mildew.